Modeling of aircraft effects on external store ejection. (August 2019) - Kozak, Mustafa Tugrul; Yildiz, Erdinc Nuri; Yazicioglu, Yigit; Cigeroglu, Ender
Modern fighter aircraft, together with their interceptor roles, are utilized as aerial bomb and long-/short-range missile carriers. Separation of those external stores from aircraft is still a challenge where the external store has to clear the carrier aircraft following the ejection process. Aircraft and store aerodynamics coupled with their individual flight conditions may result in an unsafe ejection where the store may interfere with the carrier aircraft instead of a clear separation. Store ejection is the initial phase of the launching process, which dominates the separation of the store by generating the initial conditions. Any error introduced to the store separation analysis during this phase will propagate to the complete trajectory solution, which is used for determining whether the store separation is safe or not. The objective of this paper is to present a computational methodology that includes not only the store aerodynamics but also the interactions of the store with aircraft rigid body motions and deformations, together with ejector dynamics. In this study, store aerodynamics, aircraft aerodynamics, aircraft aeroelasticity, and pylon elasticity are used to characterize the ejector dynamics for determining the ejection end-of-stroke parameters.